THE EFFECT OF SERVICE QUALITY AND SOCIODEMOGRAPHIC CHARACTERISTICS ON PATIENT SATISFACTION AT THE WIRA SATYA POLYCLINIC OF THE MOBILE BRIGADE UNIT, YOGYAKARTA SPECIAL REGION REGIONAL POLICE - Ansyar Eka Putra Anwar; Yuni Pratikno; Widya Nengsih (Journal Informatic, Education and Management (JIEM), 2026)
The purpose of this study was to analyze the effect of service quality ($X_1$) and sociodemographic characteristics ($X_2$) on patient satisfaction ($Y$) at the Wira Satya Polyclinic of the Mobile Brigade Unit, Yogyakarta Special Region Regional Police. Service quality and patients' sociodemographic characteristics were expected to influence their level of satisfaction with the healthcare services received. This study employed a quantitative method with descriptive and verificative approaches. The population comprised 375 patients who attended the Wira Satya Polyclinic of the Mobile Brigade Unit, Yogyakarta Special Region Regional Police, from August to December. The sample was determined using Slovin's formula with a 10% margin of error and selected through simple random sampling, resulting in 79 respondents. Data were collected using questionnaires and analyzed through multiple linear regression, t-tests, and an F-test with SPSS version 25. The results showed that: (1) service quality had a positive and significant effect on patient satisfaction ($p = 0.000 < 0.05$), with a partial contribution of 21.5% ($R^2 = 0.215$); therefore, H1 was accepted; (2) sociodemographic characteristics had a positive and significant effect on patient satisfaction ($p = 0.001 < 0.05$), with a partial contribution of 13.3% ($R^2 = 0.133$); therefore, H2 was accepted; and (3) service quality and sociodemographic characteristics jointly had a positive and significant effect on patient satisfaction ($p = 0.000 < 0.05$; $F_{\text{calculated}} = 42.828 > F_{\text{critical}} = 3.09$), with a simultaneous contribution of 53.0% ($R^2 = 0.530$); therefore, H3 was accepted. The remaining 47.0% was influenced by variables outside this study. Based on these findings, it can be concluded that improving service quality and understanding patients' sociodemographic characteristics can increase patient satisfaction at the Wira Satya Polyclinic of the Mobile Brigade Unit, Yogyakarta Special Region Regional Police.